The Antigastric Cancer Effect of Triptolide is Associated With H19/NF-κB/FLIP Axis - Yuan, Weiwei; Huang, Jinxi; Hou, Shanshan; Li, Huahua; Bie, Liangyu; Chen, Beibei; Li, Gaofeng; Zhou, Yang; Chen, Xiaobing (Frontiers in Pharmacology, 2022)
Background and Objective: Triptolide (TP), one of the fat-soluble components extracted from the Chinese medicinal herb Tripterygium wilfordii Hook F. (TWHF), possesses strong anti-tumor bioactivities while its dose-dependent side effects restrict its wide application. This study was designed to investigate whether inflammatory factors increased the anti-tumor effects of the non-toxic dose of TP on gastric cancer cells and tried to explore the possible mechanisms. Method: AGS and MKN45 cells were treated with different doses of TP and TNF-α. Cell viability and apoptosis were detected in vitro. Additionally, NF-κB mediated pro-survival signals and cytoprotective proteins, especially FLIP, were detected to determine their effects on TP/TNF-α-induced apoptosis. Moreover, the function of lncRNA H19/miR-204-5p/NF-κB/FLIP axis was investigated in vitro and the anti-gastric cancer effect of TP plus TNF-α was proved in the mice xenograft model. Result: In vitro experimental results showed that TP pre-treatment promoted apoptosis in AGS and MKN45 cells upon TNF-α exposure. TP/TNF-α mediated apoptosis was partly mediated by the inhibitory effect of NF-κB mediated FLIP expression. Oncogene H19 lying in the upstream pathway of NF-κB played a vital role upon TNF-α exposure and bioinformatics analysis proved that H19 participated in TP/TNF-α-induced apoptosis via binding of miR-204-5p. Lastly, low dose of TP and TNF-α inhibited the tumor weight and tumor volume of AGS and MKN45 cells in vivo. Conclusion: TP pretreatment increased apoptosis in TNF-α stimulated gastric cancer cells, which is dependent on the disruption of H19/miR-204-5p/NF-κB/FLIP axis. Co-treatment of TP and TNF-α is a better option for enhancing the anti-cancer effect and lowering the side effect of TP.